REPRESENTASI KEMAMPUAN BERBICARA (SPEAKING) DAN TATA BAHASA (GRAMMAR) SISWA SMA SEDERAJAT DI KOTA PADANG SIDEMPUAN - Rahmat Huda; Anni Zuraida, Indra Hadinata Rambe, Lanna Alisya Fitri (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study aims to determine the representation of speaking ability and grammarThe sample of this study was students in five high schools (SMA) in Padangsidimpuan, with a sampling technique by using cluster random sampling. This research is a correlation research with descriptive quantitative data collection techniques. The tool used in this study is speaking performance rubric to measure students' speaking ability, while to measure students' vocabulary mastery using the multiple choice test. To analyze the data in this study, the author used descriptive statistics (individual score, mean score) and inferential statistics (pearson product moment correlation) to calculate variables of vocabulary mastery and speaking skills. The results of this study represented that for the level of vocabulary and speaking achievement of students was at a good level. Researchers also found that there was a positive correlation between vocabulary mastery and students' speaking ability with a correlation significance of 0.943. The correlation is classified as a close correlation, meaning that the two variables have a strong correlation. Based on the results of the study, it can be concluded that the representation of students' speaking ability and vocabulary mastery is positively correlated, meaning that the highest level of vocabulary mastery then the level of speaking is also high. Therefore, teachers who play a role in controlling students in the teaching and learning process are also important to know the improvement of vocabulary and speaking ability.